ALTERNATIVE METHOD FOR REBONDED BRACKET CLEANING USING INORGANIC SOLVENT - Maringka, Gina; Irawan, Bambang; Herda, Ellyza; Masud, Zainal Alim (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to prove that organic solvents areas effective and efficient as sandblasting and burning for cleaning rebonded brackets. Methods: Thirty stainless steel metal brackets mounted on 30 maxillary first premolar teeth were categorized into three cleaning method groups, each consisting of 10 brackets. After 24 h, shear bond strength (SBS) tests were performed using a universal testing machine. Results: The one-way ANOVA test showed a significant difference (p=0.000) among the mean SBS values in the three cleaning method groups. However, the modified adhesive remnant index by a Kruskal–Wallis analysis showed no significant difference (p=0.860). The scanning electron microscopy results revealed that the organic solvent cleaning method showed better bracket performance than the other two methods. Moreover, the energy-dispersive X-ray spectroscopy results showed that the adhesive material remaining on the bracket base was relatively similar among the three cleaning methods. Conclusion: Based on practicality and the results of this study, the organic solvent cleaning method was proven to be effective and efficient. Therefore, organic solvents can be recommended as an alternative cleaning method for detached brackets.